Under the oak tree : the comic. 2 - Kim, Suji; Namu (Author); Namu (Author); Seomal; Seomal (Inklore, 2025)
"A long-awaited reunion and a fragile happiness . . . The second volume of the official webcomic based on the hit webnovel by Suji Kim. Riftan has returned from the royal capital just in time to deal with a group of rogue knights attacking the gates of Anatol. When the dust settles, he and Maxi finally have time to get to know each other properly, but Maxi struggles to show Riftan who she really is for fear that he will reject her. Even worse are her fears that the next time Riftan is called away he might never return. Determined to prove her worth and secure an unshakeable place in her new home, Maxi agrees to help the sorcerer Ruth create a new magical device. . .and discovers she might be capable of more than she could have ever dreamed."--Publisher.